On the solution of the Liouville equation over a rectangle. (1996) - Arthurs, A. M.; Clegg, J.; Nagar, A. K.
Abstract : Methods for integral equations are used to derive pointwise bounds for the solution of a boundary value problem for the nonlinear Liouville partial differential equation over a rectangle. Several test calculations are performed and the resulting solutions are more accurate than those obtained previously by other methods.